2018
DOI: 10.1002/ange.201802983
|View full text |Cite
|
Sign up to set email alerts
|

Potent Th2 Cytokine Bias of Natural Killer T Cell by CD1d Glycolipid Ligands: Anchoring Effect of Polar Groups in the Lipid Component

Abstract: Th2-biasing CD1d ligands are attractive potential candidates for adjuvants and therapeutic drugs.H owever,t he number of potent ligands is limited, and their biasing mechanism remain unclear.H erein, as eries of novel Th2biasing CD1d glycolipid ligands,b ased on modification of their lipid part, have been identified. These have shown high binding affinities and efficient Th2 cytokine production. Importantly,t he truncated acyl chain containing variants still retain their binding affinities and agonistic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…NKT cells are activated by non-peptide antigens such as glycolipids, 17,18,27,28 and structure-activity relationship studies on NKT cell activators have revealed that their structural variations influence downstream responses from NKT cells. [29][30][31] Consequently, researchers have concentrated on optimizing the structures of activators capable of eliciting desired effects from NKT cells, resulting in the identification of numerous effective activators. 32,33 These advancements have enabled NKT cell modulator applications for therapeutic agent development and vaccine adjuvants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NKT cells are activated by non-peptide antigens such as glycolipids, 17,18,27,28 and structure-activity relationship studies on NKT cell activators have revealed that their structural variations influence downstream responses from NKT cells. [29][30][31] Consequently, researchers have concentrated on optimizing the structures of activators capable of eliciting desired effects from NKT cells, resulting in the identification of numerous effective activators. 32,33 These advancements have enabled NKT cell modulator applications for therapeutic agent development and vaccine adjuvants.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 These advancements have enabled NKT cell modulator applications for therapeutic agent development and vaccine adjuvants. 31,34,35 This leading situation in NKT cell activator development underscores the significance of exploring ligand design strategies for activating MAIT cells, which are more abundant than NKT cells in humans, 17,28 and creating a diverse range of easy-to-handle MAIT cell activators that can be used as potent tools in therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to date most α-GalCer analogues have focused on modulating hydrophobic interactions of ligands and CD1d. However, there are some polar residues such as Cys12, Gln14, and Ser28 in the A′ pocket (Figure b, bottom panels), and a few studies utilized those hydrophilic residues for designing α-GalCer analogues to change the binding properties between CD1d and lipid antigens. In 2014, Kim and co-workers focused on those polar residues in the A′ pocket of CD1d, designed α-GalCer analogues containing the truncated ω-hydroxyl acyl chain (Figure a), and claimed that these analogues retained the NKT cell stimulation activity comparable with the original α-GalCer. Recently, Fujimoto and co-workers introduced an amide group in the middle of the acyl chain (Figure a) and demonstrated that the interaction between amide group and hydrophilic residues in the A′ pocket induces the Th2-selective response of cytokines in NKT cells …”
mentioning
confidence: 99%
“…To investigate the ligand–CD1d interaction, we tried to verify our design strategy using the covalent interaction between ligands and CD1d. We first incubated CD1d protein with each ligand in various reported and modified conditions, ,, and the samples were denatured and analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) to observe the covalent adducts of CD1d–ligand. But Coomassie blue staining of the gel showed only the intact CD1d protein in all samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation